Isolation and comparison of tumorigenicity of different cell populations from the MCF-7 breast cancer cell line based on CD44 and CD24 markers - Phuc, Pham Van; Keng, Siah Chia; Nguyet, Nguyen Thị Minh; Thuy, Duong Thanh; Ngoc, Phan Kim (Vietnam Journal of Biotechnology, 2012)
Breast cancer stem cells are the origin of breast tumour. Cells expressing marker CD44+CD24-/dim were considered breast cancer stem cells in human being. The aims of this study is to isolate potential candidate breast cancer stem cell from the MCF-7 cell line to find out whether it is possible to isolate cancer stem cells using two cell surface markers: CD44 and CD24. Stem-like properties were studied in vivo by observing the tumorigenicity of different cell populations in immunosuppressed mouse models. MCF-7 cells were subculture for several passages and were sorted out into 3 different cell populations by 2 specific antibodies which bind to CD44 and CD24, using flow cytometry. Cell sub-populations: CD44+, CD44+/CD24+ and CD44+/CD24-/dim were further cultured and were then analysed using flow cytometry again to determine the purity of the population. Different cell sub-populations were then harvested and injected into mouse models at two specific doses, 103 and 106 cells. Tumour formation in the mice was monitored closely and the percentages of mice which have tumour were recorded as results. The results showed that the capacity of causing tumour in mouse was highest in CD44+CD24-/dim cell population and lowest in CD44+ cell population. These results confirmed CD44+CD24-/dim cells were the strongest cell population causing tumour in breast cancer cells MCF-7.